Experience Sampling - Michaela Riediger (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Experience Sampling refers to the repeated sampling of momentary experiences in the individual's natural environment. Methodological advantages include the minimization of retrospective response biases and the maximization of the validity of the assessment. Conceptual benefits include the provision of insights into shortterm processes and into the daily-life contexts of the phenomena under study. Making use of the benefits of Experience Sampling while taking its methodological challenges into consideration allows addressing important research questions in the social and behavioral sciences with much precision and clarity. Despite this, Experience Sampling information is still rare in the data infrastructure that is publicly available to researchers. This stands in contrast to a current thriving of the methodology in research producing datasets that are not publicly available, as is the case in many psychological investigations. Following a discussion of the benefits and challenges of Experience Sampling, this report outlines its potential uses in social science and economic research and characterizes the status quo of Experience Sampling applications in currently available datasets, focusing primarily on household surveys conducted after 2001. Recommendations are given on how an intensified use of Experience Sampling in large-scale data collections can be facilitated in the future.
Keywords: 330; Experience Sampling in the social and behavioural sciences